1991
DOI: 10.1002/glia.440040602
|View full text |Cite
|
Sign up to set email alerts
|

Functions and distribution of voltage‐gated sodium and potassium channels in mammalian schwann cells

Abstract: Recent patch-clamp studies on freshly isolated mammalian Schwann cells suggest that voltage-gated sodium and potassium channels, first demonstrated in cells under culture conditions, are present in vivo. The expression of these channels, at least at the cell body region, appears to be dependent on the myelinogenic and proliferative states of the Schwann cell. Specifically, myelin elaboration is accompanied by a down regulation of functional potassium channel density at the cell body. One possibility to account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 113 publications
(185 reference statements)
3
66
0
Order By: Relevance
“…Biii, Despite a 60% attenuation of current density, the transient current component possessed voltage-dependent activation properties (Ϫ6 Ϯ 1.3 mV, n ϭ 13) identical to that seen in control treated cells. (Orkand et al, 1966;Chiu, 1991) by providing a rapid and efficient removal of ions by taking up K ϩ . In agreement with this hypothesis, Wilson and Chiu (1990) demonstrated that inwardly rectifying K ϩ channels are concentrated in Schwann cell membranes in the vicinity of the nodes of Ranvier, an area associated with the extrusion of K ϩ into the extracellular environment after action potential activity.…”
Section: Discussionmentioning
confidence: 99%
“…Biii, Despite a 60% attenuation of current density, the transient current component possessed voltage-dependent activation properties (Ϫ6 Ϯ 1.3 mV, n ϭ 13) identical to that seen in control treated cells. (Orkand et al, 1966;Chiu, 1991) by providing a rapid and efficient removal of ions by taking up K ϩ . In agreement with this hypothesis, Wilson and Chiu (1990) demonstrated that inwardly rectifying K ϩ channels are concentrated in Schwann cell membranes in the vicinity of the nodes of Ranvier, an area associated with the extrusion of K ϩ into the extracellular environment after action potential activity.…”
Section: Discussionmentioning
confidence: 99%
“…After PNS injury, Schwann cells provide a growth-promoting environment for regenerating axons through secretion of neurotrophic factors 1 and extracellular matrix elements 22 and ultimately myelinate the axons. Several groups have studied transplantation of Schwann cells after SCI and have shown successful integration of these cells in the host tissue with some regeneration of sensory axons and myelination of these axons associated with modest improvement of hindlimb function.…”
Section: Adult-derived Stem and Progenitor Cellsmentioning
confidence: 99%
“…During the last decade, a corpus of data has accumulated demonstrating that glial cells possess a wide range of ion channels (reviews by Barres, Chun & Corey, 1990;Barres, 1991;Chiu, 1991;Ritchie, 1992;Sontheimer, 1992) and neurotransmitter receptors (Barres, 1991). This prompted the idea that messages might be exchanged between glial cells and neurones.…”
Section: The Forskolin-induced Changes In Channel Behaviour (Open Andmentioning
confidence: 99%